Ab initio and long-range studies of the electronic transition dipole moments among the low-lying states of Rb2 and Cs2 molecules. (July 2016) - Pazyuk, Elena A.; Revina, Elena I.; Stolyarov, Andrey V.
Abstract: The spin allowed electronic transition dipole moments (ETDM) of rubidium and cesium dimers are calculated among the states converging to the lowest three dissociation limits. The ETDM functions are evaluated for a wide range of internuclear distances R in the basis of the spin-averaged wavefunctions corresponding to pure Hund׳s coupling case (a) by using small (including the 8 subvalence +1 valence electrons) effective core pseudopotentials (ECP). The dynamic correlation is accounted for in a large scale multi-reference configuration interaction (MR-CI) method applied to only two valence electrons. The core-polarization potentials (CPP) are implemented to implicitly take the residual core–valence effect into account. The reliability of the present EDTM functions is discussed through comparison with preceding ab initio calculations and their long range perturbation theory counterparts. The achieved accuracy allowed us to quantitatively support the asymptotic behavior of the ETDM functions predicted in Marinescu and Dalgarno (1995[4] ). The long R -range transition moments could be useful to optimize stimulated Raman processes employed in ultracold molecule production. Abstract : Highlights: Electronic transition dipole moments of Rb2 and Cs2 are ab initio calculated. The systematic error of the present results does not exceed few percent. Asymptotic behavior of the ab initio functions is close to their long range theory counterparts.